FORMULASI MEKANISME PASOKAN BAHAN JADI MELALUI PLATFORM DIGITAL PADA DANI BUTIK - Mayfa Aulia; Adi Prijuna Lubis; Sumantri Sumantri (Politeknik Ganesha Medan, 2026)
This study aims to design and implement a digital platform-based finished goods supply mechanism system at Dani Butik to enhance the efficiency of inventory management and product distribution. The main issue identified is the manual stock recording process, which leads to data inconsistencies, delayed information, and ineffective report generation. This research adopts a qualitative approach with data collection techniques including observation, interviews, and literature review. The system is developed as a web-based application using PHP and MySQL by applying the Supply Chain Management (SCM) concept. The results indicate that the proposed system is capable of integrating inventory data in real-time, improving the accuracy of recording incoming and outgoing goods, and generating timely and reliable automated reports. The implementation of this system significantly improves operational efficiency, minimizes recording errors, and supports more effective decision-making at Dani Butik.